INTERNAL STRUCTURE OF THE HYDROCHEMICAL ANOMALY AT 13° N ON THE EAST PACIFIC RISE - Gramberg I.S.; Goryainov I.N.; Ashadze A.M. (My University, 1988)
Hydrochemical methods are important in prospecting for deep-water sulfide ores in the ocean. Their efficient use and the development of techniques for interpreting the resultant data require a knowledge of the structure of hydrochemical anomalies. We report on the correlations between the concentrations of zinc in the filtrate of hydrochemical samples of bottom water collected in the vicinity of 13° N on the East Pacific Rise, where there are active hot springs. In general, the development of the hydrochemical anomaly can be represented as follows. Vicinal hydrothermal sources generate a three-dimenional turbulent patch. During its evolution, the patch collapses and spreads out laterally under the control of stratification and currents. As it collapses, the turbulent patch is converted to internal waves. The internal waves generate turbulence of a smaller scale, and so on through many scales until the turbulence and the internal waves microstructural layers on the periphery of the hydrochemical anomaly.